تحسين اتجاهات طلاب جامعة الجوف نحو دمج الأطفال - محمد جاد المولى محمد, أحمد (جامعة الوادي University of Eloued, 2016)
يهدف البحث الحالي إلى تحسين اتجاهات طلاب جامعة الجوف نحو دمج التلاميذ ذوي الإعاقات المتوسطة والشديدة في مدارس التعليم العام، وتكونت عينة البحث من(43) طالبًا بقسم التربية الخاصة في جامعة الجوف بالمملكة العربية السعودية، وصمَّم الباحث استبيانًا(12 عبارة) للتعرف على اتجاهات هؤلاء الطلاب نحو الدمج، وأعد برنامجًا معرفيًا لتحسين اتجاهاتهم، واتبع الباحث المنهج التجريبي(تصميم المجموعة الواحدة بقياس قبلي وقياس بعدي)، وأظهرت نتائج البحث فعالية البرنامج المستخدم في تحسين اتجاهات الطلاب نحو دمج التلاميذ ذوي الإعاقات المتوسطة والشديدة في مدارس التعليم العام، ولم تظهر فروق في تلك الاتجاهات تبعًا لمتغير تخصص الطلاب(إعاقة عقلية أو صعوبات تعلم)، ولا لمتغير مستواهم الدراسي(المستوى الخامس أو المستوى السادس)، واختتم البحث بمناقشة نتائجه، وعرض مجموعة من التوصيات والبحوث المستقبلية المقترحة ذات العلاقة بموضوع البحث الحالي. The current research aims to investigate the effectiveness of a program to improve Aljouf University students attitudes(n= 43) towards the integration of students with moderate and severe disabilities in public education schools in Saudi Arabia. The researcher designed a questionnaire (12 statements) to find out students attitudes towards the integration and prepared a cognitive program to improve their attitudes. The experimental method(pretest and posttest design) was used in the study. Results indicated the effectiveness of a program in improving the students attitudes towards the integration of students with moderate and severe disabilities in public education schools, and there were no differences in students attitudes due to academic specialty (intellectual disability or learning disabilities), nor significant differences due to academic grade(5th or 6th grade). The study was concluded by results discussion, a body of recommendations and future research topics were suggested.
ذوي الإعاقات المتوسطة والشديدة في المدارس العادية
مقال
Keywords: الاتجاهات نحو الدمج، المنهج التجريبي، البرامج، التربية الخاصة، الإعاقات المتوسطة والشديدة، الإعاقة العقلية; attitudes towards integration, experimental method, programs, special education, moderate and severe disabilities, intellectual disabilities.